Desenvolvimento de refrigeradores de líquido ambientalmente sustentáveis para a indústria de bebidas - Pico, David fernando Marcucci (2023)
This work presents an experimental analysis of the elimination of the refrigerant R22 and the reduction of CO2 equivalent emissions in direct expansion beverage coolers. These chillers are widely used in bars, restaurants, shopping malls, etc. to extract from the keg and chill the beverage simultaneously. These refrigeration systems use flooded-type evaporators and consequently need a high refrigerant charge to operate. The refrigerant charge can range from 950 g for a domestic application and ~6000 g for a commercial application. It is noteworthy that the most used refrigerants for this application are R22 and, to replace it, the use of R134a has increased significantly over the years. Both refrigerants are listed as substances regulated by the Montreal Protocol due to their high global warming potential (GWP), a harmful characteristic to the environment related to the greenhouse effect. To reduce the emissions of this type of refrigerant, initially, a significant reduction in the fluid charge was proposed to reduce direct contribution, furthermore, the use of R290 (HC) was proposed as a replacement for R22 for this application. A fully instrumented and automated experimental apparatus was built to simulate the beverage extractions and operation under different external conditions. The results showed that direct emissions can be reduced by up to 40% and performance can be significantly improved by refrigerant charge and capillary tube optimization on existing equipment (flooded expansion), reflected in the slight reduction of indirect emissions. To make feasible use of R290, all potential points for charge reduction in the system were mitigated and a dry expansion evaporator was developed for this application. This retrofit brought improvements such as a refrigerant charge reduction from 4500 g of R22 to 150 g of R290 and lower energy consumption of the equipment. These improvements allowed the direct emissions to be reduced by up to 99% and indirect emissions of CO2 equivalent by up to 3%.